Injury‐associated levator ani muscle and anal sphincter ooedema following vaginal birth: a secondary analysis of the EMRLD study. (7th June 2021) - Pipitone, F; Miller, JM; DeLancey, JOL
Abstract : Objective: To determine whether all three components of the levator ani muscle (pubovisceral [= pubococcygeal], puborectal and iliococcygeal) and the external anal sphincter are equally affected by oedema associated with muscle injury after vaginal birth. Design: Observational cross‐sectional study. Setting: Michigan Medicine, University of Michigan. Population: Primiparous women classified as high risk for levator ani muscle injury during childbirth. Method: MRI scans obtained 6–8 weeks postpartum were analysed. Muscle oedema was assessed on axial and coronal fluid‐sensitive magnetic resonance (MRI) scans. Presence of oedema was separately determined in each levator ani muscle component and in the external anal sphincter for all subjects. Descriptive statistics and correlation with obstetric variables were obtained. Main outcome measures: Oedema score on fluid‐sensitive MRI scans. Results: Of the 78 women included in this cohort, 51.3% ( n  = 40/78) showed muscle oedema in the pubovisceral (one bilateral avulsion excluded), 5.1% ( n  = 4/78) in the puborectal and 5.1% ( n  = 4/78) in the iliococcygeal muscle. No subject showed definite oedema on external anal sphincter. Incidence of oedema on the pubovisceral muscle was seven times higher than on any of the other analysed muscles (all paired comparisons, P < 0.001). Conclusions: Even in the absence of muscle tearing, the pubovisceral muscle shows by far the highest incidence of injury, establishing that levator components are not equally affected by childbirth. External anal sphincter did not show oedema—even in women with sphincter laceration— suggesting a different injury mechanism. Developing a databased map of injured areas helps understand injury mechanisms that can guide us in honing research on treatment and prevention. Tweetable abstract: Injury‐associated levator ani muscle and anal sphincter oedema mapping on MRI reveals vulnerable muscle components after childbirth. Tweetable abstract: Injury‐associated levator ani muscle and anal sphincter oedema mapping on MRI reveals vulnerable muscle components after childbirth.